Leptospiral antibodies in wild boars (Sus scrofa) bred in Brazil - Fornazari,F (2011)
In the recent years, the wild boar (Sus scrofa) trade has increased in Brazil. The present study aimed to detect Leptospira spp. infection in 308 blood samples from wild boars bred in São Paulo state, Brazil. The microscopic agglutination test (MAT) was performed using 29 serovars. Sixty three (63; 20.45%) animals tested positive against the serovars Hardjo (29/63; 46.0%), Copenhageni (11/63; 17.4%), Pomona (8/63; 12.7%), Pyrogenes (4/63; 6.3%), Wolfii (4/63; 6.3%), Autumnalis (3/63; 4.7%), Icterohaemorraghiae (2/63; 3.1%), and Hardjo-miniswajezak (1/63; 15.8%). These results indicate that captive wild boars were infected with Leptospira spp. and may represent a source of infection to humans and other animals.